Implementasi Pembaruan Sistem Inti Administrasi Perpajakan (Coretax) terhadap Efisiensi Kinerja Pegawai di Direktorat Jenderal Pajak - Kharisma Candra Utama; Lingga Yuliana (Master Manajemen, 2025)
This study aims to analyze the effect of the implementation of the Core Tax Administration System (CTAS) in Indonesia on tax revenue performance, specifically on the efficiency of employee performance at the Directorate General of Taxes through qualitative approach methods. The sample collection technique used purposive sampling where respondents were determined with the criteria of being employees at the Directorate General of Taxes with the position of Tax Executor and Counselor. Coretax, as a digital technology-based tax system, is expected to increase the transparency of tax information and strengthen the supervision mechanism in tax management. This study aims to show that the implementation of Coretax contributes significantly to increasing the effectiveness of employee performance at the Directorate General of Taxes and strengthening the ability of tax authorities to search for transaction data, reduce opportunities for fraud, and accelerate the audit process of tax cases. The results of the study show that Coretax is able to improve service performance faster, more efficiently and transparently and. However, the challenges in implementation practice from early January 2025 to the end of April 2025 still have system error problems that do not always run smoothly and a series of other technical problems, both from the user interface of taxpayers and tax officers themselves.